A STUDY REGARDING NUTRITIONAL STATUS AND AWARENESS DURING 1000 DAYS OF MOTHERHOOD - Chaudhari, Neeta P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Pregnancy and lactation are among the most stressful periods in the life of a woman, particularly under conditions of poverty and mal nutrition, since the mother has to provide nutrition for her and the rapidly growing fetus. Pregnancy period is crucial for baby if proper care should not taken. Health of mothers directly depends on diet and nutrition which they consume. Knowledge of nutrition and nutrients must help to maintain good health during 1000 days. Present study was aimed to study about nutritional status and awareness during 1000 days of motherhood and nutritional status. For the study, total 152 urban area’s pregnant women were randomly selected from Mehsana city. The present study was conducted with a descriptive, and survey method research design for the assessment of the nutritional status of mothers. An ideal pre structured questionnaire was prepared with suggestions of experts and used for the data collection. The blood haemoglobin data was obtained from secondary data which mentioned in Mamata card of selected mothers. Suitable statistical test was applied. 61.18 % mothers were home makers. 57.14 % mothers consumed vegetarian diet.78 % had 11-12 g/dl i.e. normal level of haemoglobin. Majority of mothers were aware and had a knowledge regarding health and nutrition for pregnancy but less aware about good weaning practices.